Arts catalyst of creative organisations for the fourth industrial revolution - Giovanni Schiuma (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
Today's digital era challenges organisations not only to follow the technological trajectories, by developing new technological solutions and/or adopting the latest disruptive technology, but most importantly to become creative and resilient organic systems that are open to changes and keen to experiment and innovate continuously. For this reason, organisations need to shape a creative environment in which technology and creativity are fully integrated and intertwined. This can be achieved by integrating the emotional and aesthetic aspects of an organisation with the technical and rational dimensions distinguishing the technology. This paper argues that, in the context of the so labelled fourth industrial revolution, successful organisations are those that exert innovative capability by becoming techno-human systems developing and melting emotional and rational knowledge. In accordance with this view, managers alongside the deployment of innovative technologies - which defines the techno-based dimensions of an organisation - they have to nurture an organisational creative environment which reflects and empowers the human-based characteristics. This can be achieved by taking into account the aesthetic dimensions and properties of an organisation and by bringing artistic projects and/or attitudes into the organisation in order to trigger critical and creative thinking. The instrumental use of the arts as a management innovation for the creation of an organisational context which nurtures human potential and creative thinking is illustrated through the analysis of some of the key arts based initiatives put in place by Elica, an Italian world leader company in the design and production of kitchen hoods.
Keywords: 650